Syawalan Lopis in Krapyak: Culinary Tradition as an Expression of Coastal Islam and Social Cohesion - Irfa Nadhifatul Ulya; Annisa Rahmalia Dardiri (Tabéq Care Center and UIN Mataram, 2025)
The Syawalan Lopis tradition in Krapyak, Pekalongan, represents an expression of coastal Muslim religiosity by integrating religious rituals, social gatherings, and local culture into a unified communal celebration held on the 8th of Shawwal. In this tradition, lopis—typically recognized as a glutinous rice delicacy in other regions—is prepared as a giant lopis that serves as the ritual centerpiece. The event involves religious leaders, descendants of the tradition’s founder, local residents, and the municipal government, transforming Krapyak annually into a communal space where the religious and cultural identity and solidarity of coastal communities are celebrated. This study analyzes the practice and interpretation of Syawalan Lopis as an expression of coastal Islam, as well as the ways in which the tradition addresses social needs and reinforces cohesion within the coastal Muslim community in Pekalongan. A descriptive qualitative approach is employed, utilizing direct observation during Syawalan, interviews with tradition bearers, and examination of documents and literature related to the history and development of Syawalan Lopis. The findings demonstrate that the giant lopis is perceived as a symbol of brotherhood, blessing, and spiritual proximity to God. The tradition of sharing lopis and participating in Syawalan is viewed as both a social and religious responsibility, which encourages community participation and sustains social cohesion. Furthermore, Syawalan Lopis facilitates microeconomic activities for local vendors and entrepreneurs and serves as a city-identity icon in religio-cultural tourism promotion. This positions the tradition as a collaborative practice of coastal Islam that integrates religious, cultural, and socio-economic interests within a communal ritual perpetuated across generations.